Partial Provability in Communication Games - Barton L. Lipman; Duane J. Seppi (Queen's University, Department of Economics, 1992)
This paper studies the ability of interested parities to communicate private information credibly to a decision maker in settings where their payoffs depend on the decision maker's action, but not on their own information per se. Examples of such situations arise in advertising, corporate control proxy contests, political debates, lobbying, and trials. Clearly, if an interested party can provide some unambiguous proof supporting his claims, then it is possible for information to be revealed despite his incentive to lie. We show that even with only very limited provability and surprisingly weak assumptions on the interested parties' preferences, full revelation of information is possible in equilibrium. We also address the role of the number of interested parities, the relationship between their preferences, and simultaneous versus sequential games in facilitating communication.
Keywords: 330